Skrinning Aktivitas Antimikroba Ekstrak Etanol Daun Mekai (Albertisia sp.): Screening of Antimicrobial Activity of Mekai (Albertisia sp.) Leaf Ethanol Extract - Nur Aini Buring Incau; Maria Almeida; Niken Indriyanti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Albertisia sp. is a plant used as eye medicine because to infection of the eye or eyelid tract by the Dayak population in Malinau Regency, North Kalimantan. This study aims to determine whether the extract of mekai leaf has antimicrobial activity as well as activity as an antibacterial or antifungal. The method that was applied this study is extraction with a maceration using 96% ethanol, followed by phytochemical analysis. The agar diffusion technique was used to test the antibacterial activity by measuring the diameter of the inhibition zone at of various extract concentrations. According to the findings, mekai leaves contain secondary metabolites such as flavonoids, alkaloids, steroids, saponins, and phenolics. In the antimicrobial test results, the ethanolic extract of mekai leaf showed activity than M.furfur has a 11,52 ± 7,97 mm, A.niger has a of 10,66 ± 1,36 mm and C.albicans has a 6,31 ± 7,04 mm. Ethanolic extracts of mekai leaf show activity than E.coli 1,59 ± 3,16 mm, P.acnes 2,45 ± 4,55 mm, S.thypii 1,69 ± 3,07 mm, and V.cholerae 1,94 ± 4,21 mm. From this study it was said that the ethanolic extract of mekai leaves might be developed as an antifungal rather than as an antibacterial.